2008
DOI: 10.1111/j.1532-849x.2007.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Color Formulation for African‐Canadian People Requiring Facial Prostheses: A Pilot Study

Abstract: Spectrophotometry and computerized color formulation provide a foundation in the color matching procedure for facial prostheses that offers objectivity to an otherwise subjective task. Through further study of spectrophotometry and computerized color formulation, and with the development of pigment databases appropriate for the African-Canadian population, it may be possible to establish a precise and repeatable color matching system that predicts required colorants and controls metamerism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
37
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 12 publications
1
37
0
3
Order By: Relevance
“…The resultant color is visually assessed against the patient's skin and adjusted until an acceptable color match is achieved. This process is technique sensitive and time consuming, and the trueness of the resultant color match is dependent on variables such as translucency, metamerism, and the subjective nature of human color perception …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant color is visually assessed against the patient's skin and adjusted until an acceptable color match is achieved. This process is technique sensitive and time consuming, and the trueness of the resultant color match is dependent on variables such as translucency, metamerism, and the subjective nature of human color perception …”
mentioning
confidence: 99%
“…This process is technique sensitive and time consuming, and the trueness of the resultant color match is dependent on variables such as translucency, metamerism, and the subjective nature of human color perception. 6 Colorimeters are capable of producing reliable and reproducible color measurements, thus removing potential variables involved in visual color assessment. 7 A light source illuminates the skin, and the intensity of the light re-emitted from the skin is analyzed and defined as tristimulus values based on a 3D color space, such as the Commission International de l'Eclairage (CIE) L*a*b* color space.…”
mentioning
confidence: 99%
“…Van Oort described these clinical problems more than 25 years ago, and suggested that the ideal solution lies in an instrumental measure of skin color with subsequent computer‐based specification of pigment formulae 1 . Part 1 of this study looked at the feasibility of using a computerized color formulation system in predicting the required colorants for mixing silicone elastomer to produce a target skin color for African‐Canadian people 2 . In Part 1, mean ΔE values (color difference between skin and silicone) decreased with iterative mixes, while pigment loading increased.…”
mentioning
confidence: 99%
“…Evaluation of computer‐based systems is central in the decision to adopt technology in treatment processes. This study, Part 2, aims to address this issue with an applied science design as follow‐up to the basic science from Part 1 of this study 2 . Specifically, in Part 2, judges rated how well each computer‐defined silicone color sample 2 matched the subject's skin on a five‐point scale to determine clinical usability of the system.…”
mentioning
confidence: 99%
See 1 more Smart Citation